Analisis Nilai-Nilai Pendidikan Moral dalam Novel Janji Karya Tere Liye - Mohamad Syafiq Mujtaba; Vava Imam Agus Faisal; Moh. Sakir (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the moral education values contained in the novel Janji by Tere Liye. A qualitative approach was employed in this research, using content analysis to examine data in the form of relevant narratives and dialogues from the novel. The analysis reveals that the novel encompasses various moral values such as honesty, responsibility, hard work, religiosity, care, tolerance, and discipline. These findings indicate that literary works, particularly novels, can serve as an effective and relevant alternative medium for moral education among adolescents and the younger generation.